The Degree of Menstrual Disturbance Is Associated With the Severity of Insulin Resistance in PCOS - Li, Xiaojia; Yang, Dongyong; Pan, Ping; Azziz, Ricardo; Yang, Dongzi; Cheng, Yanxiang; Zhao, Xiaomiao (Frontiers in Endocrinology, 2022)
Objective: Insulin resistance (IR) is an important determinant of the phenotype and morbidity of the polycystic ovary syndrome (PCOS). In this study, we aimed to figure out the association between the degree of menstrual disturbance and the severity of IR in women with PCOS. Design: It is a cross-sectional study conducted in an academic tertiary setting. Patients: Five hundred twenty-seven women diagnosed with PCOS by 2003 Rotterdam criteria and 565 controls with regular vaginal bleeding. Interventions: Medical history collection, physical examination and blood sampling. Main outcome measures: Body mass index (BMI), fasting glucose, fasting insulin, homeostatic model assessment for IR (HOMA-IR) and hormonal parameters. Results: Women with PCOS had higher level of BMI, HOMA-IR and HOMA-β than controls, with decreased level of SHBG and QUICK I index. LH/FSH, T, AFC, DHEAS, FAI, mFG and the incidence of delayed insulin peak increased with the degree of menstrual disturbance although there were no significances of the latter four parameters. Women with vaginal bleeding intervals of 45-90 days had relative higher level of HOMA-IR and HOMA-β although adjusted with age and BMI than the other two groups. Similar results were observed in AUGI and I/G. Anovulatory women with vaginal bleeding episodes of less than 45 days tended to have higher glucose and insulin level, AUCG, AUCI, HOMA-IR, HOMA-β but decreased QUICK I and Matsuda Index than those who were ovulatory. In women with vaginal bleeding intervals of longer than 45 days who had hyperandrogenism (HA) showed higher level of glucose, insulin, HOMA-IR and HOMA-β but lower QUICK I and Matsuda Index. Conclusions: In women with PCOS, the severity of IR, the LH/FSH ratio and androgen level increased with higher degree of disturbance in menstrual cyclicity (i.e., the vaginal bleeding intervals). Subgroup analysis indicated the situation of HA may aggravate the disorder of glucose metabolism in women with PCOS. Overall, the interval between episodes of vaginal bleeding may be useful as a ready measure for predicting the severity of IR in PCOS. Keywords: polycystic ovary syndrome; glucose metabolism; insulin resistance; vaginal bleeding intervals; hyperandrogenism